Analysis of Learning Motivation and Burnout of Malaysian and Chinese College Students Majoring in Sports in an Educational Psychology Perspective - Xu, Ruilin; Wang, Qinglei; Chin, Ngien Siong; Teo, Eng Wah (Frontiers in Psychology, 2021)
The purposes are to deepen the understanding of the correlation between learning motivation and learning burnout and thereby stimulate the learning motivation of college students. According to the theory of educational psychology, the mechanism of learning motivation and the causes of learning burnout are analyzed. The learning motivation and learning burnout of college students majoring in sports are taken as the breakthrough point. The learning motivation and learning burnout situation of Chinese and Malaysian students majoring in sports are surveyed and compared through questionnaires. In addition, Chinese students majoring in sports are taken as examples to analyze the impact of learning motivation on learning burnout. The correlations between various dimensions are analyzed to determine the impact of learning motivation on learning burnout. The total learning motivation scores of students from Wuhan Sports University and University of Malaya Centre for Sport & Exercise Sciences are (122.3±22.4) and (140.2±23.6), respectively, and their average scores for each question are 3.60 and 4.07, respectively. The total learning burnout scores of students from Wuhan Sports University and University of Malaya Centre for Sport & Exercise Sciences are (58.2±8.95) and (53.6±7.34), respectively. The learning motivation of Malaysian college students majoring in sports is slightly stronger than Chinese students. Compared with Malaysia, the learning burnout of college students majoring in sports in China is extra apparent, mainly exhibited in the two dimensions of depression and a low sense of achievement. The learning motivation and learning burnout of college students majoring in sports are negatively correlated; that is, the stronger the learning motivation, the weaker the learning burnout; on the contrary, the weaker the learning motivation, the more severe the learning burnout.